2013
DOI: 10.1016/j.ijgo.2013.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated features of restless legs syndrome in a population of Iranian women during pregnancy

Abstract: Restless legs syndrome is common during pregnancy and is associated with poor sleep and an increased risk of cesarean delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 22 publications
(50 reference statements)
4
46
6
Order By: Relevance
“…25 A research was conducted on Prevalence and impact of restless leg syndrome in pregnancy the result showed that there is increase prevalence of RLS in pregnant women as compared to general population. Michal Minar compared the clinical feature of idiopathic and secondary RLS among pregnant women.…”
Section: Resultsmentioning
confidence: 99%
“…25 A research was conducted on Prevalence and impact of restless leg syndrome in pregnancy the result showed that there is increase prevalence of RLS in pregnant women as compared to general population. Michal Minar compared the clinical feature of idiopathic and secondary RLS among pregnant women.…”
Section: Resultsmentioning
confidence: 99%
“…The MT [1] and MT [2] melatonergic receptor ramelteon [62,63] was found to be effective in increasing total sleep time (TST) and sleep efficiency (SE), as well as in reducing sleep onset latency (SOL) in insomnia patients [64]. The melatonergic antidepressant agomelatine, displaying potent MT [1] and MT [2] melatonergic agonism and relatively weak serotonin 5HT(2C) receptor antagonism [65,66], was found effective in the treatment of insomnia comorbid with depression [6777]. Other melatonergic compounds are currently under development [71].…”
Section: Treatment Of Menopausal Insomnia Using Melatoninmentioning
confidence: 99%
“…The levels of estrogens rise and fall almost simultaneously with the development of RLS during pregnancy, and there are studies showing that women with RLS have higher serum concentrations of estrogen than women without RLS (3), but there are also contradicting data (67). There are studies showing an association between RLS and adverse pregnancy outcomes such as increased rates of preeclampsia, cesarean delivery, and depressed mood, but data are limited (69)(70)(71). Recently a committee from the International RLS Study Group has published clinical practice guidelines for the diagnosis and treatment of RLS during pregnancy and lactation (72).…”
Section: Paradigm Of Questions For Epidemiology Studies Of Rlsmentioning
confidence: 99%